Bridge modular switched‐capacitor DC‐DC converter with soft switching operation and multilevel voltage‐gain range. Issue 9 (3rd June 2019) - Zeng, Tao; Wu, Zhen; He, Liangzong
Abstract : A bridge modular switched‐capacitor (BMSC) DC‐DC converter with soft switching operation and multilevel voltage‐gain range is proposed in this article. It is mainly composed of an interleaved booster and a switched‐capacitor circuit. The symmetrical interleaved structure is applied in the interleaved booster to obtain the ripple‐free of the input current, and the interleaved pulse width modulation control scheme is employed to achieve zero‐voltage‐switching operation of all power switches. The BMSC is employed in the switched‐capacitor circuit to achieve high step‐up gain without having to use a transformer with a high turns ratio, and it can be expanded to obtain a multilevel voltage‐gain range. In addition, the zero‐current‐switching operation of rectifier diodes can be obtained when the resonant frequency is above the operating frequency of the interleaved booster. A 400‐W prototype converter was constructed with an input voltage of 25 V. The analyses are validated by the simulation and experimental results. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.